Reading of the Week: A continuing professional development program for psychiatrists and residents that Osler would have liked - Gratzer, David; Islam, Faisal; Sockalingam, Sanjeev; Beckett, Robyn (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Introduction: William Osler started the first journal club more than a century ago. As in Osler’s, continuing professional development (CPD) is challenging to deliver in our day. This paper discusses the CPD outcomes of Reading of the Week (ROTW), an innovative online education resource aimed at Canadian psychiatrists and psychiatry residents.Methods: ROTW consists of a weekly email sent to these physicians through formal partnerships, including 13 residency training programs, and summarizes the latest literature in psychiatric care. An online survey using Moore’s continued medical education evaluation framework was conducted to determine the outcomes of ROTW and how to improve it.Results: One-third of ROTW subscribers (n = 332) responded to the survey. Respondents reported a very high rate of satisfaction (97%). The most significant findings: ROTW improved participants’ understanding of psychiatry (93%) and informed their practice (83%).Conclusions: ROTW is a program that addresses challenges related to remaining “up-to-date” amidst the vast amount of resources available. Survey data suggests that ROTW has a high satisfaction rate and achieves practice change, perhaps because it provides a boundless learning option for trainees and providers. Further research is needed better to understand the reasons for the success of this program.